Crack Up Crack Down : Slavs and Tatars : The 33rd Ljubljana Biennial of Graphic Arts. - Biennial of Graphic Arts Ljubljana 2019 (Ljubljana : International Centre of Graphic Arts (MGLC), 2019)
Abu Hamdan, Lawrence ; Ahsan, Hamja ; Apter, Emily ; Bronstein, Pablo ; Cristian, Dragos ; Erek, Cevdet ; De Othello, Woody ; Fournier, Arthur ; Koenig, Raphael ; Gutierrez, Martine ; Haliti, Flaka ; Jagodic, Stane ; Kadyrova, Zhanna ; Kanu, Dozie ; KRIWET ; Kazama, Sachiko ; Kruglyanskaya, Ella ; Madani, Tala ; Maurs, Augustin ; Metahaven ; Mul, Marlie ; Orsag, Marina ; Pirman, Alenka ; KULA ; Bostjan Gorenc - Pizama ; Ross-Ho, Amanda ; Saeed, Lin May ; Salemy, Mohammad ; Simoniti, Vid ; Smrekar, Hinko ; Top Lista Nadrealista ; Tot, Endre ; Uddenberg, Anna ; Vacheva, Martina ; Voytovich, Pavlo ; Wermers, Nicole ; Wutej, Anja ; Xaniashvili, Giorgi ; XIYADIE ; Zamojski, Honza
The book was published as a part of the 33rd Ljubljana Biennial of Graphic Arts, Crack Up - Crack Down
boek
Keywords: Slavs and Tatars